Integrating Financial Literacy Aspects in Small And Medium Enterprise Capital Budgeting - Kartika Ayu Kinanti; Ayu Nareswari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This research investigates the significant role of financial literacy in the context of capital budgeting in Micro, Small, and Medium Enterprises (MSMEs). The study focuses on the challenges faced by MSMEs in effectively managing their capital budgets, as well as the potential benefits of integrating financial literacy into their budgeting strategies. Through a comprehensive review of existing literature and case studies, this research emphasizes the importance of providing MSME owners and managers with the financial knowledge and skills necessary to make informed decisions regarding their capital investments. The study highlights various techniques and approaches to enhance financial literacy among MSMEs, emphasizing the importance of understanding financial concepts, risk assessment, and the use of appropriate budgeting tools. Furthermore, this research examines the impact of increased financial literacy on the overall financial health and sustainability of MSMEs. The research findings indicate that enhanced financial literacy can lead to more efficient capital budgeting practices, better risk management, and improved long-term growth prospects for MSMEs. This research contributes to the ongoing discourse on the role of financial literacy, capital budgeting, and the development of MSMEs, providing valuable insights for decision-makers, practitioners, and stakeholders striving to create an enabling environment for the growth of small and medium enterprises in the global economy.